Omission Lies: The Effect of Omitting Little or Much Information on Verbal Veracity Cues - Aldert Vrij; Sharon Leal; Haneen Deeb; Ronald P. Fisher (European Journal of Psychology Applied to Legal Context)

(untitled)
Background: People sometimes lie by deliberately leaving out information. Such omission lies can have different sizes: Lie tellers can deliberately omit less or more information. We examined the effect of omission size on verbal cues to deceit. Method: A total of 152 participants followed a target person during his mission in which he met two other persons. In the debrief interview, truth tellers reported all they could remember; small-omission lie tellers omitted one meeting and large-omission lie tellers omitted both meetings. The analyses focused on the parts of the mission all participants reported truthfully. We distinguished between essential information (parts of the mission surrounding the omission) and non-essential information (parts of the mission that were not close to the omission). We examined external, contextual, internal details, complications, common knowledge details, and self-handicapping strategies. We also measured participants’ strategies. Results: Truth tellers reported more complications than both groups of lie tellers in both the essential and non-essential information parts. Lie tellers were more than truth tellers inclined to keep their story simple. Conclusion: It further supports the notion that omission lie tellers are inclined to keep their stories simple and that, perhaps because of that, complications emerged as a veracity indicator.